Minimal cost design of virtual private network - Liang, Huan (University of Ottawa (Canada), 2003)
VPN technology is an attractive cost-effective solution for the support of the networking needs of enterprises. In this work, we review current issues in the development of VPN technology. We then focus our research on minimal cost design, used by network-based IP VPN service providers. The interest in such solutions is generated by both customers seeking to reduce support costs and by Internet Service Providers (ISPs) seeking new revenue sources. Solving the cost minimization would allow ISPs to define and deploy new VPN services. In this thesis, Multicommodity Min-Cost Flows (MMCF) formulations are applied to the resource allocation in network-based IP VPN, in order to develop a cost-effective routing proposal. Compared with RFC 2676, one of the Open Shortest Path First (OSPF) algorithms, various improvements in routing costs are obtained corresponding to different proposed network topologies.
Keywords: Engineering, Electronics and Electrical.